2020
DOI: 10.1186/s12989-020-00361-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum-borne factors alter cerebrovascular endothelial microRNA expression following particulate matter exposure near an abandoned uranium mine on the Navajo Nation

Abstract: Background: Commercial uranium mining on the Navajo Nation has subjected communities on tribal lands in the Southwestern United States to exposures from residual environmental contamination. Vascular health effects from these ongoing exposures are an active area of study. There is an association between residential mine-site proximity and circulating biomarkers in residents, however, the contribution of mine-site derived wind-blown dusts on vascular and other health outcomes is unknown. To assess neurovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Previous studies have shown that major heavy metals of PM 2.5 potentially accumulate in the liver (Li et al, 2015), whereas genes associated with transportation of toxic chemicals (metals and minerals) in PM 2.5 may play an important role in apoptosis and damage of liver cells (Figure 6). Notably, our KEGG analysis revealed several pathways associated with PM 2.5 resistance, namely the insulin signaling pathway, phosphatidylinositol signaling system, adrenergic signaling in cardiomyocytes, gastric acid secretion, and inflammatory mediator regulation of TRP channels, consistent with previous studies (Xu Z. et al, 2019;Sanchez et al, 2020;Zheng et al, 2020). One of the most significant pathway was that regulating mineral absorption, which comprised several genes including ATP1A2, SLC6A19, MT1M, TRPV6, and ATP1B2, indicating that the absorption of metals by the liver is essential for PM 2.5 toxicity.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that major heavy metals of PM 2.5 potentially accumulate in the liver (Li et al, 2015), whereas genes associated with transportation of toxic chemicals (metals and minerals) in PM 2.5 may play an important role in apoptosis and damage of liver cells (Figure 6). Notably, our KEGG analysis revealed several pathways associated with PM 2.5 resistance, namely the insulin signaling pathway, phosphatidylinositol signaling system, adrenergic signaling in cardiomyocytes, gastric acid secretion, and inflammatory mediator regulation of TRP channels, consistent with previous studies (Xu Z. et al, 2019;Sanchez et al, 2020;Zheng et al, 2020). One of the most significant pathway was that regulating mineral absorption, which comprised several genes including ATP1A2, SLC6A19, MT1M, TRPV6, and ATP1B2, indicating that the absorption of metals by the liver is essential for PM 2.5 toxicity.…”
Section: Discussionsupporting
confidence: 91%
“…These were considered as candidate novel miRNAs when the flank 80‐nt sequences (from genome locations) were successfully predicated to contain hairpin RNA structures by using RNAfold software (http://rna.tbi.univie.ac.at/cgi-bin/RNAWebSuite/RNAfold.cgi). 23–26 …”
Section: Methodsmentioning
confidence: 99%
“…These were considered as candidate novel miRNAs when the flank 80-nt sequences (from genome locations) were successfully predicated to contain hairpin RNA structures by using RNAfold software (http://rna.tbi.univie.ac.at/cgi-bin/RNAWe bSuit e/RNAfo ld.cgi). [23][24][25][26] The expression levels of miRNA for each mite stage and sample were calculated. The miRNA differential expression levels (as represented by normalized deep-sequencing counts) were compared across samples/groups by chi-squared test, with a significance threshold of p < .01.…”
Section: Mirnas In Different Mite Stagesmentioning
confidence: 99%
“…Circulating miRNAs have been used as effective diagnostic and therapeutic biomarkers for patients [134,136]. Significant changes in cellular murine miRNA expression have been found after exposure to ambient PM near an abandoned uranium mine, and miRNAs from cerebrovascular endothelial cells show similarity to serum-derived miRNAs [137]. Additionally, exosomes are a class of extracellular vesicles derived from endocytosis, abundant in miRNAs, released by cells, and accessible in biofluids, such as saliva, urine, and plasma.…”
Section: Non-coding Rnasmentioning
confidence: 99%